1987
DOI: 10.1002/ajmg.1320260205
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward presymptomatic testing in Huntington disease

Abstract: One hundred thirty-one individuals at 50% risk of inheriting Huntington disease (HD) responded to a survey to study their attitudes toward taking a genetic test based on the identification of a genetically linked DNA polymorphism. Ninety-six percent of the respondents believe that presymptomatic testing should be available, and 66% say they will use it themselves. Fewer married individuals, in comparison to those single, separated, and divorced, intend to take the test. Many respondents (40%) said their primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 21 publications
8
64
1
4
Order By: Relevance
“…44 A strong tendency for people to self-select themselves in or out of testing on the basis of their beliefs about their anticipated response to the test result has been observed in the clinical literature. 45,46 The suggestion also is supported by some psychological theories, particularly those based on subjective expected utility theory, 47,48 which argue that outcome expectancies-defined as an individual's expectations about the outcomes or consequences of …”
Section: Resultsmentioning
confidence: 96%
“…44 A strong tendency for people to self-select themselves in or out of testing on the basis of their beliefs about their anticipated response to the test result has been observed in the clinical literature. 45,46 The suggestion also is supported by some psychological theories, particularly those based on subjective expected utility theory, 47,48 which argue that outcome expectancies-defined as an individual's expectations about the outcomes or consequences of …”
Section: Resultsmentioning
confidence: 96%
“…The questionnaire was constructed by drawing on items used in other published studies after an extensive literature review on adult onset neurodegenerative disorders (Quaid et al 1989;Tan et al 2007;Evers-Kiebooms et al 1987;Mastromauro et al 1987;Quaid 2999). The questionnaire contained 41 items in four sections: demographic information, knowledge about genetics and PD, attitudes about genetic testing for PD, and genetic information services (see supplementary information).…”
Section: Methodsmentioning
confidence: 99%
“…4 Although early surveys indicated that predictive testing would be requested by 66 -79% of individuals at risk for HD 5,6 worldwide uptake currently ranges between 3 and 24% among at-risk individuals. 7 The most frequently cited reasons for declining predictive testing have been the absence of a cure, concerns about coping and the fear of genetic discrimination (GD).…”
Section: Introductionmentioning
confidence: 99%